CHANGING OF SILICA VALVES OF DIATOM SYNEDRA ACUS subsp. RADIANS INFLUENCED BY PACLITAXEL - Bedoshvili, Ye D; Gneusheva, K V; Likhoshway, Ye V (T͡S︡itologii͡a, 2017)
Diatoms are unicellular microscopic eukaryotes able to form species-specific frustules with micro- and nanostructures of biogenic silica. The morphogenesis of frustules components occurs intracellularly within special organelles under control of cytoskeleton. The mechanisms of morphogenesis control are not clear. The influence of paclitaxel, the microtubule inhibitor, onto morphogenesis of valve of pennate diatom Synedra acus subsp. radians was investigated. It has been shown that microtubule disturbance on the early morphogenesis stages provoke symmetry axis displacement of immature valve followed by curvature of the valve. At subsequent stages of morphogenesis stages, disturbance of the fine silica micro- and submicroscale structures (areolae and velums) occurs. It is supposed that a necessary condition for successful diatom valve morphogenesis is a balance between stable and dynamic microtubules.